Influenza A virus infection in Japanese wild boars (Sus scrofa leucomystax) - SHIMODA, Hiroshi; NGUYEN, Dung VAN; YONEMITSU, Kenzo; MINAMI, Shohei; NAGATA, Nao; HARA, Nanami; KUWATA, Ryusei; MURAKAMI, Shin; KODERA, Yuuji; TAKEDA, Tsutomu; YOSHIKAWA, Yasuhiro; HORIMOTO, Taisuke; et al. (Journal of Veterinary Medical Science, 2017)
Serum samples were collected from 385 wild boars between 2010 and 2013 to examine the seroprevalence of influenza A virus (IAV) in Japan. Antibodies against IAV were identified using a commercial kit in 13 wild boars (3.4%). To identify the serotypes, positive sera were examined by virus-neutralization test using representative serotypes and strains. Three wild boars in Yamaguchi and four in Tochigi showed the highest antibody titers against the pandemic H1N1 2009 virus and classical swine H1N1 virus strains, respectively. These data indicate that wild boars may have close contact with humans and domestic pigs and therefore that there is potential for IAVs to reassort in wild boars as they have been shown to do in pigs.